(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to clarify the reality of the independence of the judiciary and its legal basis, and to clarify the guarantees that guarantee its continuity and the non-invasion of other authorities into it. The researcher studied these foundations in detail, based on the urgent need to clarify the foundations and characteristics that characterize the Islamic judiciary in terms of independence and achievement. The researcher presented a detailed study of these principles with an indication of the guarantees for their realization, which reflects the extent of the advancement of Islamic thought and Islamic civilization. The researcher reached many findings and recommendations represented in the fact that the judiciary in Islam in thought, system, and mechanisms is the ideal model for achieving justice, independence, and preserving human rights. The results also showed that the judiciary has principles and guarantees that must be applied. Hence, the researcher recommends working to achieve the principles and guarantees of the judiciary in practice.